Ecological and social constraints are key for voluntary investments into renewable natural resources. (July 2020) - Fujitani, Marie L.; Riepe, Carsten; Pagel, Thilo; Buoro, Mathieu; Santoul, Frédéric; Lassus, Rémy; Cucherousset, Julien; Arlinghaus, Robert
Highlights: We model voluntary investments by members of civil society into the environment. We analyze 1, 809 freshwater resource management arrangements in Germany and France. Follow SES framework aim 'dissect and harness complexity'; boosted regression trees. Social-ecological and governance context, norms and bottom-up social pressures key. Context, incentives eclipse knowledge, cognitions for some pro-environmental actions. Abstract: Encouraging pro-environmental behavior is an urgent global challenge. An interdisciplinary framework covering governance, economic, social, ecological, and psychological dimensions is required to understand the salient features that encourage pro-environmental outcomes within and across contexts. We apply the Ostrom social-ecological systems framework to model voluntary investments by members of civil society into the aquatic environment. Using a data set of 1, 809 angling clubs managing water bodies for fish stocking and habitat management in Germany and France, we show that a small set of factors, most crucially social-ecological and governance context as well as social norms and other bottom-up social pressures, drive environmental investments. These factors appear to override behavioral influences from psychological variables of the decision-maker. By contrast, the contextual setting related to property rights, size of the resource system, and social expectations were found to be strongly related to behavioral decisions, highlighting that the social-ecological context as well as incentives may be more important than knowledge and cognitions in driving certain pro-environmental actions.